Modeling an Object Oriented for Maintenance Purposes (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2012)
Software maintenance is the last phase of the software life cycle. The aim of the software maintenance is to maintain the software system in accordance with advancement in software and hardware technology. In this paper, we discuss a maintenance system for object-oriented techniques. The paper therefore discusses about a problems in object oriented techniques under the maintenance environment. These problems include understanding object oriented system, complex dependencies in object-oriented system, inheritance, polymorphism and dynamic binding problem that maintainers and developers commonly face. Finally, we talk about the proposed object-oriented maintenance tool.